2003
DOI: 10.1021/ic0203926
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Chelation of Metal Ions by Ethylenediaminetetraacetate Intercalated in a Layered Double Hydroxide

Abstract: The solid-state chelation of transition metal ions (Co(2+), Ni(2+), and Cu(2+)) from aqueous solutions into the lithium aluminum layered double hydroxide ([LiAl(2)(OH)(6)]Cl x 0.5H(2)O or LDH) which has been pre-intercalated with EDTA (ethylenediaminetetraacetate) ligand has been investigated. The intercalated metal cations form [M(edta)](2)(-) complexes between the LDH layers as indicated by elemental analysis, powder X-ray diffraction, and IR and UV-vis spectroscopies. If metal chloride or nitrate salts are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…When the Mg/Al molar ratio is increased to 3.0, with the exception of a weak shoulder on the (006) reflection peak centered at 2θ ≈ 12°, the reflections are characteristic of a single phase with a basal spacing of 1.254 nm. The elemental analysis results also www.eurjic.org [32,23] On this basis O'Hare et al [6] proposed that the interlayer of LiAl 2 -[MY] LDH consists of a monolayer of metal-edta complexes with the maximal dimension of each anion perpendicular to the hydroxide layers. This model, with the heavy metal atom located at the midpoint of the interlayer galleries, is not consistent with the observed inversion of the relative intensities between the (006) and (009) reflections in the LDH-2.0- [MY].…”
Section: Effect Of Varying the Layer Charge Density On The Orientatiomentioning
confidence: 99%
See 1 more Smart Citation
“…When the Mg/Al molar ratio is increased to 3.0, with the exception of a weak shoulder on the (006) reflection peak centered at 2θ ≈ 12°, the reflections are characteristic of a single phase with a basal spacing of 1.254 nm. The elemental analysis results also www.eurjic.org [32,23] On this basis O'Hare et al [6] proposed that the interlayer of LiAl 2 -[MY] LDH consists of a monolayer of metal-edta complexes with the maximal dimension of each anion perpendicular to the hydroxide layers. This model, with the heavy metal atom located at the midpoint of the interlayer galleries, is not consistent with the observed inversion of the relative intensities between the (006) and (009) reflections in the LDH-2.0- [MY].…”
Section: Effect Of Varying the Layer Charge Density On The Orientatiomentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] O'Hare et al [6] have recently prepared LDHs containing such complexes, either directly by intercalation of the transition metal-edta complex or indirectly by forming the metal complex in situ in the interlayer galleries of Li-Al LDH pre-intercalated with edta. Tsyganok et al [7] have studied the catalytic activity in dry reforming of methane of a material derived from LDH-intercalated [Ni(edta)] 2-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic guest entities, like monomers and polymers [11,12], functional biomolecules [13,14], and complexes of reducible transition metals [15,16] have been intercalated within an LDH matrix. LDH nanocomposites have found applications in mechanical strengthening [11,12], as adsorbents [17], or magnetic nanostructures [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…LDH nanocomposites have found applications in mechanical strengthening [11,12], as adsorbents [17], or magnetic nanostructures [15,16]. In contrast, their potential usage as fire retardants has not been widely explored.…”
Section: Introductionmentioning
confidence: 99%
“…LDHs exhibit a well-defined layered structure with relatively large surface area, high porosity, high layer charge density and interlayer anion mobility [18]. Therefore, LDHs have been extensively employed as catalysts, ion exchangers, and adsorbents [19][20][21][22]. Recently, we have found that the galleries of the LDH could lead to the concentration of the CL reactants/ intermediates on the surface or in the interlayer of the LDHs, facilitating the occurrence of the CL reactions [23,24].…”
Section: Introductionmentioning
confidence: 99%